4(y-2)+11=13

Simple and best practice solution for 4(y-2)+11=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y-2)+11=13 equation:



4(y-2)+11=13
We move all terms to the left:
4(y-2)+11-(13)=0
We add all the numbers together, and all the variables
4(y-2)-2=0
We multiply parentheses
4y-8-2=0
We add all the numbers together, and all the variables
4y-10=0
We move all terms containing y to the left, all other terms to the right
4y=10
y=10/4
y=2+1/2

You can always share this solution

See similar equations:

| 3(6y)-y=75 | | 10(6n+2-n)=70 | | 4.5+10m=8.47 | | (h-10)/(2)=-7 | | 3x+6=x+5x | | -14+6n=-8(8n-7) | | 5v^-36v=32 | | 4p-8=14 | | p-(p/6)=(p/3)+2 | | 4x-2x-10=-9+5x-5 | | 2n+11=1+n+3 | | 21(2-2)+12x=44 | | -2(y-1)+5(1-y)=77 | | -7p-9=-16-6p | | 248=-8(-7+8p) | | x+1=-19 | | 6x^2x-1=0 | | 5.x/5=3/x-2 | | 6j+7=-5 | | 3x-12=2x+12+x | | -4-x+7x=56 | | 2w-4w-32=10w | | 15/x+9=3/4 | | 5d/1440=3 | | 2(2x+16)=-(5x-2)+7 | | 5d/1440=5 | | 5(2x+7)=-9+14 | | 5=6+m/14 | | 17-1/5(20s+15)=-5s-10 | | | | | | Z=-6+5i | | -7(2x-6)+5(3x-4)-2=9-3 |

Equations solver categories